Sporidesmioides thailandica gen. et sp. nov. (Dothideomycetes) from northern Thailand - Li J. (2017)
© 2016, German Mycological Society and Springer-Verlag Berlin Heidelberg. Sporidesmioides thailandica gen. et sp. nov., isolated from herbaceous litter in northern Thailand, is described and illustrated. The new genus is characterised by sporidesmium-like, septate, solitary, acrogenous, pale brown to brown, obclavate, conidia, which taper towards the apex and are truncate at the base and septate conidiophores similar to those of Sporidesmium species in Sporidesmiaceae (Sordariomycetes). It differs from similar genera by the presence of a stromatic base, polyblastic conidiogenous cells and a distinct, colourless sheath at the conidial apex. Phylogenetic analyses of combined LSU, SSU, TEF1-α and RPB2 sequence data show that the new taxon, Sporidesmioides thailandica, forms a separate, single clade with Torulaceae in Pleosporales, Dothideomycetes, and is distinct from Sporidesmiaceae (Sordariomycetes).